Coalition for African Rice Development (CARD) initiative contributes to increase production by 103% in Sub-Saharan Africa (SSA) - CGIAR Research Program on Rice (2019)
Coalition for African Rice Development (CARD) was initiated with the aim to double rice production over the period 2008 to 2018. CARD was led by Japan with the support of many institutions including Africarice. After 10 years of implementation, we assessed the impact of CARD on rice production. CARD has contributed to increase production by 103% in 23 countries in Sub-Saharan Africa (SSA).